Electrochemical and structural characterization of nanocomposite Agy:TiNx thin films for dry bioelectrodes: the effect of the N/Ti ratio and Ag content. (20th January 2015) - Pedrosa, P.; Machado, D.; Fiedler, P.; Alves, E.; Barradas, N.P.; Haueisen, J.; Vaz, F.; Fonseca, C.
Highlights: Agy :TiNx thin films were sputtered with different N/Ti atomic ratios and Ag contents. The electroactive area increases (1000-fold) with increasing N/Ti atomic ratios. The films display impedances <10 kΩ at the 1–50 Hz interval (EEG range). No Ag surface segregation was visible in the under-stoichiometric samples. The samples with N/Ti atomic ratio = 0.3 (15 at.% Ag) and 0.7 (32 at.% Ag) are the most appropriate for bioelectrode applications. ABSTRACT: Agy :TiNx nanocomposite thin films sputtered with different N/Ti atomic ratios and Ag atomic contents were characterized from the structural and morphological points of view. Their electrochemical behaviour was studied in a synthetic sweat solution, aiming at selecting a suitable material for biolectrode applications. An increase of the N/Ti atomic ratio, which is accompanied by an increase of the Ag atomic content, leads to a substantial increase of the roughness and porosity of the samples, especially for N/Ti ratios >0.2. For N/Ti atomic ratios up to 0.3 (15 at.% Ag) no metallic Ag segregation is visible in the TiNx matrix. Hence, the possible formation of TiAg and Ti2 Ag intermetallics or even a Ag/TiAg/Ti2 Ag phase mixture, although not demonstrated, should not be disregarded. As for the N/Ti atomic ratio = 0.7 (32 at.% Ag) sample, the Ag phases are predominantly concentrated near the interface with the substrate. The amount of Ag phases at the surface of the films remains somewhat low for all TiN under-stoichiometric films, even for Ag atomic contents up to 32 at.%. When the TiNx matrix reaches the stoichiometric condition (sample with N/Ti atomic ratio = 1 and 20 at.% Ag), Ag segregation occurs and metallic Ag aggregates are visible at the surface of the film, leading to a substantially different electrochemical behaviour. The impedance of the Agy :TiNx films in synthetic sweat solution is mainly ruled by the roughness/porosity variation, thus the higher the N/Ti atomic ratio, the lower the impedance. The interfacial film/sweat electrochemical noise and drift were similar for all films and comparable to the results obtained for commercial Ag/AgCl electrodes (except for the N/Ti atomic ratio = 1 and 20 at.% Ag film). In view of the results, it may be concluded that the samples with N/Ti atomic ratios = 0.3 (15 at.% Ag) and 0.7 (32 at.% Ag) are the most appropriate for further bioelectrode development.